2023
DOI: 10.1002/bin.1936
|View full text |Cite
|
Sign up to set email alerts
|

Teaching children with autism spectrum disorder to tact auditory stimuli: A replication

Abstract: It is important that tacts are controlled by stimuli across all senses but teaching tacts to children with autism spectrum disorder (ASD) is often limited to visual stimuli. This study replicated and extended a study on the effects of antecedent‐stimulus presentations on the acquisition of auditory tacts. We used a concurrent multiple probe across sets design and an embedded adapted alternating treatments design to evaluate acquisition of auditory tacts when auditory stimuli were presented alone (i.e., isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In four of these studies, a preference could not be established for at least one participant due to responses being allocated across multiple initial links. That is, there was no consistent selection of the same stimulus (Bergmann et al, 2023; Galizio et al, 2020; Lozy et al, 2020; Mandel et al, 2022). Two of these studies indicated a lack of a control condition as a limitation (i.e., Bergmann et al, 2023; Galizio et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In four of these studies, a preference could not be established for at least one participant due to responses being allocated across multiple initial links. That is, there was no consistent selection of the same stimulus (Bergmann et al, 2023; Galizio et al, 2020; Lozy et al, 2020; Mandel et al, 2022). Two of these studies indicated a lack of a control condition as a limitation (i.e., Bergmann et al, 2023; Galizio et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…That is, there was no consistent selection of the same stimulus (Bergmann et al, 2023; Galizio et al, 2020; Lozy et al, 2020; Mandel et al, 2022). Two of these studies indicated a lack of a control condition as a limitation (i.e., Bergmann et al, 2023; Galizio et al, 2020). Therefore, it may be useful to include a control from the outset of the assessment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations